COMMUNITY-BASED RAPID BIODIVERSITY ASSESSMENT: A PRELIMINARY STUDY IDENTIFYING POTENTIAL NATURAL RESOURCES IN KOTA AGUNG UTARA SOCIAL FORESTRY, TANGGAMUS - Elly Lestari Rustiati; I Gede Swibawa; Jani Master; Alvin Wiwiet Susanto; Rendi Hasarudin; Joko Suprianto; Supriyadi Supriyadi; Edi Edi; Tugino Tugino; Andi Aryandinata; Dian Neli Pratiwi; Indra Kurniawan; Okta Saputra; Intan Diani Fardinatri; Mariman Mariman (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2023)
Community-based rapid biodiversity assessment has been done initially with Gapoktanhut Lestari Sejahtera, a group of coffee farmers practises social forestry in protected forest, Sedayu, Semaka, Tanggamus, under supervision of KPH Kotaagung Utara, Tanggamus. Its aim is to identify potential natural resources in Kotaagung Utara protected forest, Tanggamus, under Kaidenren Nature Conservation Fund, in collaboration with University of Lampung and Rainforest Alliance program. Direct survey and observation were done, kobotoolbox was applied to collect the biodiversity information, the direct and indirect data of plants, animals as well as landscapes. Of 480 data input has been done by transect line from November, 2021 to February, 2022 covering 15 observed areas. The data consists of direct and indirect data of plants, animals as well as landscapes. The finding done is by local names included plants (n=78) mostly understory plant species, orchids, and ferns, small animals (n=40) include amphibians, reptiles, birds, and arthropods, indirect signs (n=11) of food remains, footprints, voices, scraps, wallowing ponds, scratches, nests, insects body remains, eggs and animals’ trail, some fungi, and landscapes. The findings shows that local community is potential citizen research resources, supporting social forestry practice and the initial building of Kota Agung Utara Forest Management Unit database